Ways to Reduce the Effect of Inflation on the Country's Economy (Eurasian Research Bulletin, 2023)
This article analyzes the scientific theoretical aspects of inflation, the aspects that are neglected in its prevention, and the dynamics of inflation in Uzbekistan and world practice. By the way, the levels of factors affecting inflation are determined, also, relevant conclusions and recommendations are given.